Perjanjian Penyelesaian Sengketa pada Pengadaan Barang dan Jasa Survei Status Gizi Indonesia Tahun 2024 (Studi Kontrak antara Kemenkes dan PT. Sucofindo) - Arifin, Mohammad Syamsul; Arrisman, Arrisman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Government procurement contracts for goods and services are public legal instruments that are prepared to ensure legal certainty, accountability, and financial protection of the state. In its implementation, contracts often undergo changes due to the technical and operational dynamics outlined in the contract addendum. The implementation of the 2024 Indonesian Nutrition Status Survey (SSGI) has experienced various technical and operational obstacles that require contract adjustments through several addendums, including the addition of honorariums for the Regency/City Technical Person in Charge (PJT). The problem arose when the Financial Audit Agency found an overpayment and recommended a return to the state treasury, thus giving rise to a difference in legal interpretation regarding the validity of the addendum. This study uses normative legal research methods with a statutory and conceptual approach, supported by empirical data as a complement to the analysis. The results of the study show that contract addendum can legally be used as an instrument for amending agreements and alternative non-litigation dispute resolution, but in the context of government procurement, its applicability is limited by the principles of legality, accountability, and compliance with state financial management. Addendum that does not meet an adequate legal and administrative basis cannot be used as a valid basis for payment.